HERZBERG HYGIENE THRORY ON ADMINISTRATIVE STAFF PRODUCTIVITY IN NNAMDI AZIKIWE UNIVERSITY AWKA (Journal of the Management Sciences, 2026)
This study is concerned with the application of Herzberg’s hygiene theory on administrative staff productivity in Nnamdi Azikiwe University. The aim is to understand how Herzberg’s hygiene factors (with emphasis on organizational policy and working environment) affect the career switch from administrative cadre to lectureship cadre, often termed “conversion”. Qualitative method was used and relying on interview of personnel managers at Nnamdi Azikiwe University as a case study. It was found that the unfavorable application of the Nnamdi Azikiwe University’s conditions of service on the administrative staff informed the career switch because they feel dissatisfied and want to be more appreciated. It was also found that poor working condition (office space) for the administrative staff was another reason for the career switch. It is therefore recommended that a review of the application of the University’s Conditions of Service as it applies to the administrative staff and also provision of adequate office space will help to reduce dissatisfaction.
Keywords: Herzberg's hygiene theory; administrative staff; productivity; career switch; organizational policy; working environment